2006
DOI: 10.1002/biof.5520270107
|View full text |Cite
|
Sign up to set email alerts
|

Croton lobatus, an African medicinal plant: Spectroscopic and chemical elucidation of its many constituents

Abstract: The chemical constituents of the African medicinal plant Croton lobatus were elucidated and characterised using 1D and 2D-NMR analysis and the application of the technique of High Resolution Electron Ionization Mass Spectrometry (HREIMS) and High Resolution Mass Spectrometry (HRMS). The novel triglyceride lobaceride or 3-((6Z,9Z)dodeca-6,9-dienoyloxy)-2-octanoyloxypropyl (6Z,9Z)dodeca-6,9-dienoate, along with ten compounds were isolated from the stems and leaves of Croton lobatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In ancient times humans used various plants and herbs that grew in their environment to treat various illnesses. Medicinal plants have emerged as some of the most widely studied plants and significant interest has been shown in their chemistry because of their potential application in medicine [1][2][3] . Many of these medicinal plants contain chemical constituents that could cause harmful effects to human if taken in large quantities.…”
Section: Introductionmentioning
confidence: 99%
“…In ancient times humans used various plants and herbs that grew in their environment to treat various illnesses. Medicinal plants have emerged as some of the most widely studied plants and significant interest has been shown in their chemistry because of their potential application in medicine [1][2][3] . Many of these medicinal plants contain chemical constituents that could cause harmful effects to human if taken in large quantities.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage composition of the alkaloids, flavonoids, saponins, phenols and tannins in the leaves of C. lobatus water extract is presented in the Table II. This study revealed that C. lobatus contains carbohydrates, glycoside, saponins, steroids, triterpenes, flavonoids and tannins as contained in other species of Croton (Attioua, 2005;Burkill, 1985;Chabert et al, 2006;Farnsworth, 1969;Willaman and Li, 1970). Croton lobatus L. contained 5.22 % alkaloid that was classified into five different types by Barthelemy et al (2012).…”
Section: Phytochemical Studiesmentioning
confidence: 85%
“…Chabert et al [35] isolated geranylgeraniol, betulinic acid, cholestan-3-one, 9,12,15octadecatrienoic acid methyl ester, 3-(4-methoxy phenyl)-2-phenyl acrylic acid, tetramethyl tetraentetracosanoic acid, octadecadienoic acid, tetramethyl-hexadeca tetraenyl ester, lobaceride, cholestan-5,7-dien-3-ol, ergosterol, 3-hydroxycholes-5-en-7-one, N-(2-hydroxy-1-phenylpropyl) benzamide from leaves and stems of A. lobata (Table 3) (Table 3). Attioua et al [10] isolated palmitanoide, onosmin B, onosmin A, N-(2-hydroxy-1-phenylpropyl) benzamide and aurentiamide acetate from aerial parts of A. lobata (Table 3).…”
Section: Chemical Composition Of Astraea Lobatamentioning
confidence: 99%